The experience of God : being, consciousness, bliss - Hart, David Bentley (Yale University Press, 2013)
Despite the recent ferocious public debate about belief, the concept most central to the discussion "God" frequently remains vaguely and obscurely described. Are those engaged in these arguments even talking about the same thing? In a wide-ranging response to this confusion, esteemed scholar David Bentley Hart pursues a clarification of how the word "God" functions in the world's great theistic faiths. Ranging broadly across Judaism, Christianity, Islam, Vedantic and Bhaktic Hinduism, Sikhism, and Buddhism, Hart explores how these great intellectual traditions treat humanity's knowledge of the divine mysteries. Constructing his argument around three principal metaphysical "moments"--Being, consciousness, and bliss -- the author demonstrates an essential continuity between our fundamental experience of reality and the ultimate reality to which that experience inevitably points.